Številčni razvoj Slovencev na Madžarskem v luči zgodovinskih dogodkov in pričevanj anketirancev v Sombotelu - Kovács, Attila (Razprave in gradivo - Inštitut za narodnostna vprašanja (1990), 2003)
The article presents a short demographic history of Slovenes in Hungary from 1941 to 2001, with special emphasis on Szombathely, the administrative, economic and cultural center of the Železna županija/Vas megye. The analysis of census data showed that the number of persons with Slovene as their mother tongue decreased by one third in the above mentioned period, mostly due to assimilation processes. The survey of Slovene or Slovene mother tongue settlements indicated that in 1941 90% of all declared Slovenes lived in the Porabje/Raba region, which is the area of autochthonous settlement of Slovenes in Hungary. However, 60 years later, only one half of this number still lives there. The other half of people with Slovene as mother tongue in 2001 lived in other parts of the state, mostly Budapest, Szombathely, Mosonmagyarovar. Most of them moved from the territory of their autochthonous settlement, especially after 1948. The emigration of the Porabje Slovenes was affected primarily by two reasons, political and economic. Unlike Porabje, the number of Slovenes in Szombathely kept increasing from 1941 to 2001. All the respondents from Szombathely originate from the Porabje, and have mostly emigrated for economic reasons.
Keywords: Hungary; Madžarska; Porabje; narodne manjšine; Hungarian Slovenes; Porabski Slovenci; narodna identiteta; demografski razvoj; demografska statistika; statistični podatki